In silico docking and comparative ADMET profile of different glycogen synthase kinase 3 beta inhibitors as the potential leads for the development of anti-Alzheimer drug therapy - Manisha Prajapat; Phulen Sarma; Nishant Shekhar; Hardeep Kaur; Sanjay Singh; Subodh Kumar; Harpinder Kaur; Saniya Mahendiratta; Amit Raj Sharma; Sukhmandeep Kaur; Vidya M Mahalmani; Bikash Medhi (Wolters Kluwer Medknow Publications, 2020)
Glycogen synthase kinase 3 beta (GSK3 β) plays a key role in pathologic hyper phosphorylation of tau and plays an important role in the pathogenesis of Alzheimer's disease. In the present study, we have screened a set of potential hits in in silico platform to gain insight regarding binding profile with the target (GSK3 β) from molecular docking, ADME/T, and molecular dynamics (MD) simulations. The three screened compounds 6-BIBEO, 6-BIO, and SB216763 topped the docking score chart when subjected to hard scoring function extraprecision of GLIDE. The active site dynamics study through MD simulations provides insights on residues Asp133, Val135, and Ile62 which are in a state of minimum deviation from their mean special position while they interact with the respective ligands. The same molecules also displayed favorable pharmacokinetic profile, negative Ames test and falls correctly within drug-likeliness rules. These agents can be taken forward further for the development of anti-Alzheimer's drug therapy.